2020
DOI: 10.1128/jcm.00772-20
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 by Use of the Cepheid Xpert Xpress SARS-CoV-2 and Roche cobas SARS-CoV-2 Assays

Abstract: SARS-CoV-2, a novel coronavirus responsible for a December 2019 outbreak in Wuhan, China, causes a syndrome characterized by fever, cough, and dyspnea progressing to acute respiratory distress syndrome (1).…

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
130
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(146 citation statements)
references
References 8 publications
13
130
1
2
Order By: Relevance
“…Of the multiple EUA assays for diagnosis of SARS-CoV-2, only the Xpert Xpress, the ID NOW, and the Accula are CLIA-waived (6). Recent data support the test performance of the Cepheid Xpert SARS-CoV-2 assay, with agreement over 99% compared to high-complexity EUA assays (8, 16, 17). In contrast, some studies have raised concern regarding the diagnostic accuracy of the ID NOW, with positive percent agreement ranging from 75-94% compared to reference assays (8–10, 18).…”
Section: Discussionmentioning
confidence: 77%
“…Of the multiple EUA assays for diagnosis of SARS-CoV-2, only the Xpert Xpress, the ID NOW, and the Accula are CLIA-waived (6). Recent data support the test performance of the Cepheid Xpert SARS-CoV-2 assay, with agreement over 99% compared to high-complexity EUA assays (8, 16, 17). In contrast, some studies have raised concern regarding the diagnostic accuracy of the ID NOW, with positive percent agreement ranging from 75-94% compared to reference assays (8–10, 18).…”
Section: Discussionmentioning
confidence: 77%
“…Another POC diagnostic that received the FDA's EUA is the Accula SARS-CoV-2 test, a handheld device that also uses PCR technology to detect SARS-CoV-2 in throat and nasal swab specimens. Specimens are added to a buffer to solubilize the samples 30,31 One study (comparing Xpert Xpress, ID NOW, and the ePlex systems) found that although all 3 had 100% specificity (did not exhibit false-positive results), Xpert Xpress performed well and had the lowest limit of detection and highest sensitivity, whereas the ePlex and ID NOW had lower sensitivities. 32 Another study determined that the POC test (ID NOW) was less sensitive compared with the traditional RT-PCR assay.…”
Section: Assay Performance and Limitationsmentioning
confidence: 99%
“…Anyway, clinical or hygiene-related decisions based on positive results of the ARIES SARS-CoV-2 Assay should consider its limits of detection which are considerably higher than the ones of the automated Cepheid approach [ 11–16 ]. This is of particular importance in situations when maximum sensitivity is desired, both for clinical decision making or surveillance purposes.…”
Section: Discussionmentioning
confidence: 99%
“…With positive molecular SARS-CoV-2 test results within less than 10 minutes, the isothermal Abbott ID Now (Abbott Laboratories, Abbott Park, Illinois, USA) approach is presently the most rapid well evaluated molecular point-of-care-testing assay for the diagnosis of COVID-19 but it is outperformed regarding sensitivity by PCR-based assays [ 7–10 ]. One well-evaluated, highly sensitive automated PCR-based testing approach is the cartridge-based Xpert Xpress SARS-CoV-2 Assay (Cepheid, Sunnyvale, California, USA) with a limit of detection of less than 100 copies [ 11-16 ].…”
Section: Introductionmentioning
confidence: 99%